2006
DOI: 10.1007/s00248-006-9161-6
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Monitoring of Microbial Population Dynamics During Operational Periods of Anaerobic Hybrid Reactor Treating Cassava Starch Wastewater

Abstract: This study characterized the microbial community and population dynamics in an anaerobic hybrid reactor (AHR) treating cassava starch wastewater. Methanogens and nonmethanogens were followed during the start-up and operation of the reactor, and linked to operational and performance data. Biomass samples taken from the sludge bed and packed bed zones of the AHR at intervals throughout the operational period were examined by 16S rRNA fluorescence in situ hybridization (FISH). The start-up seed and the reactor bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 30 publications
3
12
0
Order By: Relevance
“…Methane yields were similar to those reported by Paixão et al and Boonapatcharoen et al who reported yields of 0.240 L CH 4 · g −1 COD removed and 0.220 L CH 4 · g −1 COD removed , however the authors used cassava wastewater loads of 5 g COD · L −1 · d −1 and 6 g COD · L −1 · d −1 with 4‐day of HRT. The present results seem more promising, since Paixão et al employed a two‐phase reactor and Boonapatcharoen et al used a single‐phase reactor, though with a 4 day HRT.…”
Section: Resultssupporting
confidence: 93%
See 2 more Smart Citations
“…Methane yields were similar to those reported by Paixão et al and Boonapatcharoen et al who reported yields of 0.240 L CH 4 · g −1 COD removed and 0.220 L CH 4 · g −1 COD removed , however the authors used cassava wastewater loads of 5 g COD · L −1 · d −1 and 6 g COD · L −1 · d −1 with 4‐day of HRT. The present results seem more promising, since Paixão et al employed a two‐phase reactor and Boonapatcharoen et al used a single‐phase reactor, though with a 4 day HRT.…”
Section: Resultssupporting
confidence: 93%
“…Treating cassava wastewater in a single‐phase hybrid reactor (37 °C), Boonapatcharoen et al found VFA/TA ratios ranging from 0.69 to 0.94, with COD removal efficiencies ranging from 84 to 94 % using OLR of 1 to 6 g COD · L −1 · d −1 , which are lower than those employed in the present investigation. The authors operated the reactor at 37 °C with the alkalinity buffer adjusted to 2.0 g · L −1 using sodium bicarbonate, however with a HRT of 8 to 4 days, much higher than that applied in the present study. Evaluating the stability of a single‐phase anaerobic reactor for the treatment of cassava wastewater, Dias et al report VFA/TA ratios of 0.298, 0.211, 0.265, and 0.776 respectively, using OLR of 1.28, 1.57, 2.68, and 2.93 g COD · L −1 · d −1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several authors had pointed out that the composition of the microbial community influences the stability and performance of anaerobic reactors, hence the importance of understanding such communities as well as the interactions within, for the effective operation and improvement of the reactor's performance [10,11,18]. These microbial interactions are particularly important in biofilm reactors, and are greatly influenced by the ability of microorganisms to attach to the support at the operational conditions applied to the reactor.…”
Section: Introductionmentioning
confidence: 99%
“…This reactor configuration also allows the operation without the need for recirculat ion or temperature conditioning, except in regions whose average temperatures are less than 25° (Peixoto et al, 2011). Another advantage of the system is that it can be used the support mean occupying only a part of the useful volu me of the reactor, which in relation to other configurations reduces costs (Boonapatcharoen et al, 2007;Peixoto et al, 2011).…”
Section: Introductionmentioning
confidence: 99%